Francesarie – Molière’s comedies adapted into the Dubrovnik dialect and their contemporary descendant – comparing and confrontation - Lovrić Jović, Ivana (Molière u hrvatskoj kulturi, 2024)
The paper analyzes the language of the comedy Šmigalove furbarije, a contemporary adaptation of Molière’s piece written by Luko Paljetak. His language has been compared to the theatre works that inspired the author, especially to francesarie from the 18th century. Through the phonological, morphological, syntactic, and lexical levels, the paper explores the possibility of realizing Paljetak’s language in the reality.